Marketing management : - Peter, J. Paul (McGraw-Hill/Irwin, 2007)
Marketing Management, 8/e, by Peter and Donnelly, serves as an overview for critical issues in marketing management. The text strives to enhance knowledge of marketing management and advance student skills so they can develop and maintain successful marketing strategies. The text does this through comprehensive text chapters that analyze the marketing process and gives students the foundation needed for success in marketing management, and through 40 cases (12 of them new, many others updated) that go beyond traditional marketing principles and focus on the role of marketing in cross-functional business and organization strategies.